The Crosstalk Between Tumor-Associated Macrophages (TAMs) and Tumor Cells and the Corresponding Targeted Therapy - Ge, Zhe; Ding, Shuzhe (Frontiers in Oncology, 2020)
Tumor microenvironment (TME) is composed of tumor cells and surrounding non-tumor stromal cells, mainly including tumor associated macrophages (TAMs), endothelial cells, and carcinoma-associated fibroblasts (CAFs). The TAMs are the major components of non-tumor stromal cells, and plays an important role in promoting the occurrence and development of tumors. Macrophages originate from bone marrow hematopoietic stem cells and embryonic yolk sacs. There is close crosstalk between TAMs and tumor cells. With the occurrence of tumors, tumor cells secrete various chemokines to recruit monocytes to infiltrate tumor tissues and further promote their M2-type polarization. Importantly, M2-like TAMs can in turn accelerate tumor growth, promote tumor cell invasion and metastasis, and inhibit immune killing to promote tumor progression. Therefore, targeting TAMs in tumor tissues has become one of the principal strategies in current tumor immunotherapy. Current treatment strategies focus on reducing macrophage infiltration in tumor tissues and reprogramming TAMs to M1-like to kill tumors. Although these treatments have had some success, their effects are still limited. This paper mainly summarized the recruitment and polarization of macrophages by tumors, the support of TAMs for the growth of tumors, and the research progress of TAMs targeting tumors, to provide new treatment strategies for tumor immunotherapy.